Gambaran Alur Donor Plasma Covid Konvalesen di Unit Donor Darah PMI Kota Yogyakarta - Francisca Romana Sri Supadmi (Akper Kesdam I/Bukit Barisan Padang, 2021)
Until now, there is no specific therapy to treat Covid-19. Various preventive measures have been taken to prevent the spread of COVID-19 infection, but new cases and deaths from Covid-19 still exist. Clinical trials of the use of convalescent plasma for the treatment of Covid-19 patients stated that it was less effective, so WHO did not recommend its further use. The rapid rate of virus mutation and the uneven distribution of vaccines in Indonesia have raised concerns about new variants. Convalescent Plasma Therapy during the pandemic remains a wiser alternative therapy to treat Covid-19 patients due to new virus variants that are different from before. This study is a descriptive study, aiming to see how the flow of convalescent plasma donors in the blood donor service unit. The study population was all convalescent plasma donors who came to donate blood at the time of the study. The research sample was selected by 38 people by accidental sampling. The results showed that convalescent plasma blood donors went through several stages starting from the donor recruitment process, general donor selection and special additional selection for convalescent plasma donor requirements, then after passing, plasma retrieval was carried out using the apheresis method. There were 38 donors, consisting of 87% male and 13% female. According to blood type, the majority were dominated by blood type O rh positive as much as 38%.